2021
DOI: 10.3390/polym13111680
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Gelatin/Silver Nanoparticles Composites Films for Biodegradable Food Packaging Applications

Abstract: The food packaging industry explores economically viable, environmentally benign, and non-toxic packaging materials. Biopolymers, including chitosan (CH) and gelatin (GE), are considered a leading replacement for plastic packaging materials, with preferred packaging functionality and biodegradability. CH, GE, and different proportions of silver nanoparticles (AgNPs) are used to prepare novel packaging materials using a simple solution casting method. The functional and morphological characterization of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 55 publications
(76 reference statements)
5
39
0
Order By: Relevance
“…Antioxidant and antimicrobial AgNPs synthesized by using Mussaenda frondosa leaves extract were loaded into gelatin/chitosan composite films that enhanced the shelf life of vegetables and fruits. From an ecological point of view, the use of biodegradable AgNPs films may reduce synthetic plastics consumption and environmental harm and may promote healthy foods [209]. In another study, Myxobacteria virescens synthesized AgNPs were impregnated into fruit wrapping paper, which increased the shelf life of apples up to 15 days as compared with the non-impregnated wrapper [210].…”
Section: Food Packagingmentioning
confidence: 99%
“…Antioxidant and antimicrobial AgNPs synthesized by using Mussaenda frondosa leaves extract were loaded into gelatin/chitosan composite films that enhanced the shelf life of vegetables and fruits. From an ecological point of view, the use of biodegradable AgNPs films may reduce synthetic plastics consumption and environmental harm and may promote healthy foods [209]. In another study, Myxobacteria virescens synthesized AgNPs were impregnated into fruit wrapping paper, which increased the shelf life of apples up to 15 days as compared with the non-impregnated wrapper [210].…”
Section: Food Packagingmentioning
confidence: 99%
“…In recent decades, a considerable number of packaging films have been developed using biopolymers, such as proteins, and polysaccharides. More recently, the combination of clays, nanostructures, and other innovative materials has been studied for novel packaging applications [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In addition to biopolymers, plant-derived bioactive compounds—such as essential oils, minerals, carotenoids, vitamins, and polyphenols, among others—have been used to modify the films’ antioxidant, antimicrobial, and physicomechanical properties [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the PLA-TA10 film had a swelling degree of 0.32%, while swelling degree of the neat PLA was 0.24%. It is found that the observed higher swelling degree of the PLA-TA10 film compared to the neat PLA is associated with increasing hydrophilicity and water retention capacity by introducing the TA plasticizer to PLA (Ediyilyam et al, 2021;Sanyang et al, 2016).…”
Section: Swelling Degreementioning
confidence: 97%